On the LiFe1-xMnxPO4 (x = 0, 0.4, 0.6, 0.65, 1) olivine-type cathode materials for lithium ion batteries. (2022) - Bezza, I.; Aziam, H.; Saadoune, I.
Abstract: Since the breakthrough findings of Goodenough et al. in 1997, extensive research was carried out on olivine-type LiMPO4 (M: Transition metal) cathode materials for lithium ion batteries. This study reports the synthesis of five compounds LiFe1-x Mnx PO4 (x = 0, 0.4, 0.6, 0.65, and 1) using sol–gel method at 800 °C. The crystal structure and the electrochemical properties of LiFe1-x Mnx PO4 versus Li + / Li were investigated. LiFe1-x Mnx PO4 materials crystallize in the orthorhombic system with P nma as space group. Moreover, a slight increase in the cell volume was noticed with the increasing amounts of Mn due to its large ionic radii (where Fe 2+ ions (0.78 Å) and Mn 2+ ions (0.80 Å). LiFe0.4 Mn0.6 PO4 shows the best electrochemical performances delivering a reversible discharge capacity of 110 mAh g −1 for 10 cycles at C/20 although no effective carbon coating was performed on the particles of this phosphate.